Implementasi Mbkm Dalam Bentuk Pelatihan E-Commerce Untuk Mewujudkan Digital Ekonomi Masyarakat Di Desa Druju Kecamatan Sumbermanjing Wetan Kabupaten Malang - Yoyok Seby Dwanoko; Roni Alim Ba’diya Kusufa; Riril Mardiana Firdaus (Jurnal ABM Mengabdi, 2022)
The Independent Learning Campus Program (MBKM) is part of a policy to implement independent learning from the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia (KEMENDIKBUDRISTEK RI). One form of this MBKM is to provide assistance to rural communities to realize the digital economy. In building a digital village, the important thing is a commitment between the government and village officials, SMEs and SMEs in the village and the village community to make the village a village that has a digital economy. Based on the results of the study of the potential development of Druju Village, Sumbermanjing Wetan District, it is still necessary to increase knowledge of human resources, so the role of academics is needed to provide economic digital literacy in rural communities. This service explains about community service programs through the development of fostered villages based on digital entrepreneurs in Druju Village, Sumbermanjing Wetan District in the form of e-commerce training. The method used is the initial survey, training, mentoring, monitoring and evaluation. The initial survey conducted focused on the potential of villages engaged in the SMEs and MSMEs, understanding the digital economy in the community, as well as problems that exist in the community related to the marketing of SME and MSME products. The initial survey was reviewed to provide training and assistance according to the needs of the community in managing the e-commerce web. With this method, it is hoped that it can help develop the digital economy of the village and solve problems that exist in the community in increasing the distribution of their product marketing, besides that this service also explains the importance of digital literacy for the village economy for the community as an important role holder in developing the village economy of Druju, Sumbermanjing Wetan District. Malang Regency